2023
DOI: 10.1111/jnc.15954
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid‐β exposed astrocytes induce iron transport from endothelial cells at the blood–brain barrier by altering the ratio of apo‐ and holo‐transferrin

Stephanie L. Baringer,
Avraham S. Lukacher,
Kondaiah Palsa
et al.

Abstract: Excessive brain iron accumulation is observed early in the onset of Alzheimer's disease, notably prior to widespread proteinopathy. These findings suggest that increases in brain iron levels are due to a dysregulation of the iron transport mechanism at the blood–brain barrier. Astrocytes release signals (apo‐ and holo‐transferrin) that communicate brain iron needs to endothelial cells in order to modulate iron transport. Here we use iPSC‐derived astrocytes and endothelial cells to investigate how early‐disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 68 publications
(129 reference statements)
0
2
0
Order By: Relevance
“…Importantly, such microglial population was found solely in high-pathology load subjects with Thal phase V and Braak stage V/VI, suggesting that microglial involvement of iron accumulation may occur in later stages [37]. Parallelly, exposure to Aβ was shown to elicit iron homeostatic changes in astrocytes [39], and single-cell RNA sequencing revealed ferroptosis genes to be significantly dysregulated in AD entorhinal cortex astrocytes [40], suggesting that AD-related iron dysregulation may be a dynamic process involving multiple cell types throughout disease progression. This could be a possible explanation for the lack of MRI iron level differences observed in MCI versus AD patients [21,31], as well as the persistence of iron cognition correlations without bulk changes in regional iron levels in AD patients, as will be discussed in more depth in the following sections [18,22].…”
Section: Cellular Iron Dysregulation In Admentioning
confidence: 94%
See 1 more Smart Citation
“…Importantly, such microglial population was found solely in high-pathology load subjects with Thal phase V and Braak stage V/VI, suggesting that microglial involvement of iron accumulation may occur in later stages [37]. Parallelly, exposure to Aβ was shown to elicit iron homeostatic changes in astrocytes [39], and single-cell RNA sequencing revealed ferroptosis genes to be significantly dysregulated in AD entorhinal cortex astrocytes [40], suggesting that AD-related iron dysregulation may be a dynamic process involving multiple cell types throughout disease progression. This could be a possible explanation for the lack of MRI iron level differences observed in MCI versus AD patients [21,31], as well as the persistence of iron cognition correlations without bulk changes in regional iron levels in AD patients, as will be discussed in more depth in the following sections [18,22].…”
Section: Cellular Iron Dysregulation In Admentioning
confidence: 94%
“…Primary astrocytic culture from mice demonstrated increased expression of ferritin upon Aβ 1-42 exposure [48]. Moreover, Aβ exposure to iPSc-derived astrocytic culture resulted in increased iron uptake by astrocytes, as well as an increase in apo-Tf secretion, which led to a three-fold increase in iron transport across the blood-brain barrier (BBB) model of EC cells [39]. In this study, the authors also demonstrated that exposure of EC to media containing classic A cytokines did not elicit changes in iron transport, suggesting that increased iron transport was not due to reactive astrocytes but due to Aβ-induced astrocytic alterations in iron regulation.…”
Section: Hypothesis 1 231 Iron Accumulation Is a Consequence Of Patho...mentioning
confidence: 99%
“…During Alzheimer's disease, cells respond to pathological conditions by increasing their acquisition of iron. Recently, it was shown that amyloid β lowers iron levels in conditioned media from iPSC-derived astrocytes, which may have been due to greater iron uptake by these cells and an elevation in their mitochondrial activity [25]. Furthermore, the conditioned media had an increased percentage of apo-transferrin, which stimulated endothelial cells to increase iron transport [25].…”
Section: Processes Accounting For Increased Iron Accumulationmentioning
confidence: 99%
“…Recently, it was shown that amyloid β lowers iron levels in conditioned media from iPSC-derived astrocytes, which may have been due to greater iron uptake by these cells and an elevation in their mitochondrial activity [25]. Furthermore, the conditioned media had an increased percentage of apo-transferrin, which stimulated endothelial cells to increase iron transport [25]. In support of this, the expression of transcripts for transferrin was upregulated in the olfactory bulb of patients with early Alzheimer's disease compared to control subjects [5].…”
Section: Processes Accounting For Increased Iron Accumulationmentioning
confidence: 99%